DEVELOPMENT, TESTING AND IMPLEMENTATION OF AN INNOVATIVE DEVICE FOR DETECTION OF SHREDDERS IN A GUN WOUND - Черняк, Віктор; Саленко, Олександр; Орел, Вадим; Карпенко, Костянтин; Приємська, Вікторія (SWorldJournal, 2025)
Existing methods for diagnosing foreign bodies (FB) in a gunshot wound are based on the differences in certain physical properties of the tissues of biological objects from inorganic fragments and substances, which are manifested in the magnetic and diel